Fabrication and critical current density studies of dip coated multi-core high-temperature superconductor tapes / Ahmad Kamal Hayati Yahya and Faizah Md. Salleh - Yahya, Ahmad Kamal Hayati; Md. Salleh, Faizah (2005)
In this work T11212/Ag tapes were fabricated using superconducting powders prepared from different nominal compositions and subjected to a combination of thermal and mechanical treatments. The effect of the thermo-mechanical treatments on transport critical current density (Jc) in zero field and in low external magnetic fields was investigated. The superconducting core of the tapes were made of Tl-1212 powder prepared from Tl0.9Bi0.1Sr1.9Mo0.1Ca0.9Y0.1Cu2O7, Tl0.9Cr0.1Sr2Ca0.9Pr0.1Cu2O7, Tl0.5Pb0.5Sr1.8Yb0.2CaCu2O7 nominal composition which were synthesized by conventional solid state technique and Tl0.8Bi0.2Sr2Ca0.8Y0.2Cu2O7 nominal composition synthesized by co-precipitation method. It was observed that different thermo-mechanical treatment on the tapes resulted in different values of Jc. J0 enhancement was observed for tapes annealed at temperatures > 870 °C in combination with intermediate mechanical rolling. Generally the yc's observed for T11212/Ag tapes using conventional-solid-state derived superconducting powder were between 500-600 A/cm2. For multi-core Tl0.5Pb0.5Sr1.8Yb0.2CaCu2O7 tapes, J0 was generally found to increase with number of core. For Tl0.8Bi0.2Sr2Ca0.8Y0.2Cu2O7 tapes fabricated using co-precipitation derived powder, the highest transport Jc of 6,538 A/cm2 at 40 K in zero field was achieved for the tape annealed at 870°C for 60 minutes. The higher magnitude of Jc is attributed to enhanced grains contact within the oxide core of the tapes as observed from its partial melted microstructure. However, for multi-core Tl0.8Bi0.2Sr2Ca0.8Y0.2Cu2O7 tapes, Jc was found to decrease with number of core. The magnetic field dependence of Jc for most tapes exhibited weak links dominated behavior for low fields (B< 0.1-0.2 T) and strong link transport behavior at higher fields. The major cause for the low Jc observed for the dip-coated tapes are believed to be mainly due to absence of favourable texturing of the tapes core. However, the Jc values for the tapes in this study are comparable to previously reported Jc values of T11212/Ag tapes fabricated via the oxide powder-in-tube method.